Time ‎‎truncated double acceptance sampling plan for the Nadarajah-Haghighi distribution - Mehran Naghizadeh Qomi; Zainalabideen Al-Husseini; Sanku Dey (Statistics, Optimization & Information Computing, 2024)
In this article, we design a double acceptance sampling plan for the Nadarajah-Haghighi (NH) distribution when the lifetime is truncated. The minimum sample sizes necessary to ensure a certain mean lifetime for selected acceptance numbers and consumer's confidence levels are obtained. The operating characteristic function and the associated producer's risks are studied. We also analyze the minimum ratios of the mean life to the specified life. Real data and simulated examples are provided to illustrate the results of the paper.